Role of 2-[18F] fluoro-2-deoxy-D-glucose-positron emission tomography/computed tomography in the post-therapy surveillance of breast cancer. - Hong-Tai Chang; Chin Hu; Yu-Li Chiu; Nan-Jing Peng; Ren-Shyan Liu (PLoS ONE, 2014)
To evaluate the usefulness of 2-[18F] fluoro-2-deoxy-D-glucose-positron emission tomography/computed tomography (FDG-PET/CT) in the early detection of breast cancer tumor recurrences and its role in post-therapy surveillance.FDG-PET/CT was performed on patients with increased serum CA 15-3 levels and/or clinical/radiologic suspicion of recurrence. A group of asymptomatic patients who underwent FDG-PET/CT in the post-therapy surveillance of breast cancer served as the controls. The results were analyzed based on the patients' histological data, other imaging modalities and/or clinical follow-up. Recurrence was defined as evidence of recurrent lesions within 12 months of the FDG-PET/CT scan.Based on elevated serum CA15-3 levels (n = 31) and clinical/radiologic suspicion (n = 40), 71 scans were performed due to suspected recurrence, whereas 69 scans were performed for asymptomatic follow-up. The sensitivity and specificity of FDG-PET/CT were 87.5% and 87.1% in the patients with suspected recurrence and 77.8% and 91.7% in the asymptomatic patients. The positive predictive value in the patients with suspected recurrence (mainly due to elevated serum CA 15-3 levels) was higher than that in asymptomatic patients (P = 0.013). Recurrences were proven in 56.3% (40/71) of the patients with suspected recurrence and in 13% (9/69) of the asymptomatic patients (P < 0.001). FDG-PET/CT resulted in changes in the planned management in 49.3% (35/71) of the patients with suspected recurrence and 10.1% (7/69) of the asymptomatic patients (P < 0.001). After follow-up, 77.5% (55/71) of the patients with suspicious recurrences and 97.1% (67/69) of the asymptomatic patients were surviving at the end of the study (P < 0.001).FDG-PET/CT was able to detect recurrence, and the results altered the intended patient management in the post-therapy surveillance of breast cancer. FDG-PET/CT should be used as a priority in patients with increased serum CA 15-3 levels, or with clinical/radiologic suspicion of recurrence, and might be useful for asymptomatic patients.